Peran Literasi Dalam Pembangunan Nasional - Faizah, Amalia Nur; Nurkomariyah, Risa; Dwiky Denova, Moh. Alfito; Mas’odi, Mas’odi (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper examines the critical role of literacy, including digital literacy, in Indonesia’s national development. This qualitative, literature-based study shows that literacy—beyond reading and writing skills—is a key factor in improving the quality of human resources, economic growth, and community welfare. However, unequal access to education and low interest in reading are major obstacles. This paper recommends the development of integrated and community-based literacy programs, improvement of educational infrastructure, and collaboration between government, educational institutions, and communities. Integration of moral values into literacy programs is also considered important for shaping the character and responsibility of citizens. In conclusion, improving literacy is a key driver of sustainable national development in Indonesia.